Ausência do pai ao longo do desenvolvimento ontogenético e indicadores de desconto de futuro: uma contribuição da psicologia evolucionista - Batista, álvaro da Costa (2010)
The new Evolutionary Psychology (E. P.) paradigm has been trying to understand how the human beings make their decisions over time regarding the most diverse variables, always bearing in mind that such a cognitive process is due to a complex natural selection process that occurred millions of years ago. One of the main topics discussed by this new paradigm is the issue of parental investment, i.e., the care the parents provide to an offspring at the expense of the investment into a new one. The present work sought to integrate these two topics, trying to understand how some variables modulate the process of decision making in a sample of the city of Natal, Rio Grande do Norte state. It was investigated the hypothesis that the presence of both parents, along the individual development, could signal a more favorable environment, providing clues to the individual that he could assume a competitive position at the socio-biological market. His decisions, therefore, could be guided by long-term investments with aims to obtain more robust rewards. On the contrary, those who has suffered for some moment the absence of one the parents could develop theirselves in a not so competitive way, starting to choose immediate benefits - but lesser ones -, since the future would be less predictable due to their worse development conditions. This study involved 152 individuals from three higher education institutions, one of them being public and the others being private ones. In the results found, there was no difference between children of coupled parents and children of deceased or divorced parents concerning discount rates. The levels of hopelessness did not affect the discount rates of children of single parents when compared to children of coupled parents. Not having one of the parents because of divorce made the child to tend to present lower scores in the domain of social relations of WHOQOL - Bref, whilst the absence of the father by death made the scores lower in the domain of environment. The results indicate that loosing one of the parents along the development influences the individual's quality of life perception, but the measurement method of future discounting rates by means of financial choices is not sensitive to this variation